Spinal Muscular Atrophy Type IIIb Complicated by Moyamoya Syndrome: A Case Report and Literature Review - Li, Jing; Li, Xin; Wang, Liqun; Wu, Guode (Frontiers in Cellular Neuroscience, 2022)
Spinal muscular atrophy (SMA) is an inherited disorder characterized by degeneration of motor neurons and symmetrical muscle weakness and atrophy. Moyamoya syndrome (MMS) or moyamoya disease (MMD) is radiologically defined by chronic cerebrovascular occlusion with abnormal vascular network formation in the skull base. We report herein a 21-year-old female patient with limb weakness and muscular atrophy for 17 years. Electromyography revealed extensive motor neuron damage. Cranial MRA showed occlusion of bilateral anterior and middle cerebral arteries, with increased peripheral blood vessels and collateral circulation. She was diagnosed as SMA type IIIb combined with MMS following genetic testing, in which homozygous deletion of exons 7 and 8 of survival motor neuron (SMN)1 gene and 3 copies of exons 7 and 8 of SMN2 gene were detected. After treatment, the patient's symptoms improved. Our study found that the rare SMA and MMS co-exist. We speculated that the moyamoya phenomenon may be related to the abnormal regulation of intracranial vascular endothelial cells and smooth muscle cells in proliferation and differentiation caused by functional defects of SMN protein. The relationship between the two diseases needs to be further elucidated in future clinical work.